THE CHANGING INTERACTION PATTERNS IN FAMILY IN THE MOUNT OF KERINCI KAYU ARO AREA, KERINCI REGENCY, JAMBI PROVINCE - Rahmawati, Tri Nurza (Kementerian Pendidikan dan Kebudayaan, 2021)
This article explained and described the changing interaction patterns in the family in the Mount of Kerinci Kayu Aro area, Kerinci Regency, Jambi Province. The theory used in analyzing the research finding was the social changing theory by Veblen and Ogburn as technocrat in materialistic perspective. This research used descriptive qualitative approach and the informants were chosen by using purposive sampling technique. Data were collected through interview, observation, and documentation. Data were analyzed through interactive analysis technique proposed by Miles and Huberman consisting of data reduction, data display, and conclusion. Data showed that the people in the Kerinci mount area was a change of interaction from directly interaction (face to face) into gadget interaction. Therefore, it could be concluded that family function was decreased. It was caused by the using of gadget, thus the interaction of parents to their children was not run well, because communication, connection, support and role of parents were no longer maximally done.Â